2015
DOI: 10.1002/jrs.4689
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-resolved and polarized Raman scattering from a single Si nanowire

Abstract: We report spatially‐resolved and polarized Raman scattering results from a single Si nanowire (NW). Transmission electron microscope images show that the surface morphology of the Si NW varies from smooth to rough along the long axis. As the NW grows, the smooth surface becomes rough because of Au diffusion to the surface, resulting in the formation of facets and stacking faults. Spatially‐resolved Raman spectra along the NW long axis reveal variations in tensile strain related to the morphological changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…studied spatially‐resolved and polarized Raman scattering from a single Si nanowire (NW). Despite the formation of facets and stacking faults, polarized Raman scattering results both from the top and bottom segments of the NW are consistent with the Raman polarization selection rules expected for a cubic crystal . Tang and co‐workers used Au nanorod‐coated Fe 3 O 4 microspheres as SERS substrates for pesticide analysis by near‐infrared laser excitation.…”
Section: Nanomaterialssupporting
confidence: 62%
“…studied spatially‐resolved and polarized Raman scattering from a single Si nanowire (NW). Despite the formation of facets and stacking faults, polarized Raman scattering results both from the top and bottom segments of the NW are consistent with the Raman polarization selection rules expected for a cubic crystal . Tang and co‐workers used Au nanorod‐coated Fe 3 O 4 microspheres as SERS substrates for pesticide analysis by near‐infrared laser excitation.…”
Section: Nanomaterialssupporting
confidence: 62%
“…For this purpose, Raman spectroscopy is widely employed to measure uniaxial stresses in NWs with a series of studies specifically addressing Si NWs. , Although Raman techniques have demonstrated a strain up to 4.5% in Si NWs patterned on highly strained silicon-on-insulator (sSOI) substrates, ,,, the level of strain reported for Si NWs fabricated on stress-free substrates is limited to 0.048% . In addition to Raman spectroscopy, X-ray diffraction approaches have been utilized to measure strain in Si NWs.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, Raman spectroscopy is widely employed to measure uniaxial stresses in NWs 18−20 substrates, 11,21,22,24 the level of strain reported for Si NWs fabricated on stress-free substrates is limited to 0.048%. 23 In addition to Raman spectroscopy, X-ray diffraction approaches have been utilized to measure strain in Si NWs. For example, a strain rate of 0.04% was measured, whose origin was traced back to the catalyst residues used during the growth processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among a suite of available characterization tools, Raman spectroscopy is a non-destructive technique that can provide insights into the effects of shape, structure, and composition of semiconductor structures (i.e., thin films [22], nanowires [23], and quantum dots [24]) on physical properties (i.e., phonon confinement and surface optical phonon modes [25, 26]). Polarization-dependent Raman scattering measurements on single semiconducting nanowires revealed that highly anisotropic shapes of nanowires have angular dependences of Raman active modes and scattered intensities (i.e., Si [27], GaAs [28], InAs [29, 30], GaP [31, 32], ZnO [33], GaN [34]). Recent advances of Raman spectroscopy technique further achieved the single-molecule level sensitivity of Raman signals through the exploitation of near-field surface resonances [35, 36] using engineered substrates with roughened metal-coated two-dimensional surface (i.e., metal nanoparticle–decorated substrate [37]) or in the form of zero-dimensional metal particles (i.e., core-shell nanoparticles [35]).…”
Section: Introductionmentioning
confidence: 99%